Allergic contact stomatitis from homeopathic preparations (Arsenicum Album 30c) used as prophylaxis against COVID 19: A case report - C J Sanjay; Karthikeya Patil; S Viveka; Nagabhushana Doggalli (Wolters Kluwer Medknow Publications, 2023)
Contact stomatitis or stomatitis venenata is defined as an oral mucosa contact allergy caused by persistent contact with a pathogenic substance. Arsenic album 30 was advised as a "preventive and prophylactic remedy" against coronavirus disease-19 (COVID-19) by The Ministry of AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha, and Homeopathy), Government of India. We present a case of a 68-year-old man who suffered ulcers on the left buccal mucosa and tongue after taking arsenic album 30c for 10 days sublingually. This is, to the best of our knowledge, the first recorded incidence of allergic contact stomatitis caused by a homeopathic drug used to treat COVID-19. This case report emphasizes the need for obtaining a history, being aware of the composition of any new items, and reporting allergies or medicines provided to the patient.